Pengembangan Modul Interaktif Berbasis Augmented Reality Pada Materi Bangun Ruang Kelas V Sekolah Dasar - Rifa’atul Mahmudah; Musabihatul Kudsiah; Zulfikar Ahmadi; Rohini, Rohini (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2023)
This research aims to develop interactive modules based on augmented reality on grade 5 building materials as a teaching tool in delivering lesson materials and supporting the learning process carried out at SDN 2 Kelayu Selatan in the 2022/2023 school year. This research is a research and development (Research and Development) using the ADDIE development model which consists of 5 steps, namely (1) analysis, (2) design, (3) development, (4) implementation, (5) evaluation. This study was conducted on grade 5 students with a total of 11 students. This research and development instrument uses validation sheets and student response questionnaires. The results of the media expert validation test with a total score of 94 are in the range of X > 79.68 scores in the "very good" category. The results of the material expert validation test with a total score of 92 are in the range of X > 79.68 scores in the "very good" category. The results of the questionnaire of student responses to the validity and effectiveness of using the module developed by comparing "yes" and "no" answers, obtained a "very good" response with a percentage of "yes" answers as much as 96.6% overall.